(untitled) (Eurasian Journal of Learning and Academic Teaching, 2025)
This article discusses the formation of a new style in music and its place in musical culture. A new style is accompanied by new ideas and techniques, forms and expressions in music. It introduces innovative approaches to the process of creating music. This article discusses the characteristics of a new style in music, the stages of its development and the change in musical genres